1985
DOI: 10.1029/jc090ic03p04819
|View full text |Cite
|
Sign up to set email alerts
|

Gulf Stream meanders: Observations on the deep currents

Abstract: During 1979–1980, an array of inverted echo sounders (IES) and three deep current meter moorings were deployed on the continental slope 100–200 km northeast of Cape Hatteras, North Carolina. This array continuously monitored the path of the Gulf Stream and the deep currents under it. The mean currents at two sites 1000 m off the bottom near the northern edge of the stream were veered to the right of the mean surface path, indicating a deep inflow to the stream. Mean currents 500 and 1000 m off the bottom 50 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…During July-November 1982, 135-day records were obtained from an array of three inverted echo sounders (lESs) and six current meters deployed in the Gulf Stream 150 km northeast of Cape Hatteras, N.C. These measurements supplement an earlier data set collected during 1979-80 in this same region (Johns and Watts, 1985; hereafter JW85), but were designed to sample a larger extent of the deep water column than had been done previously. It was hoped that, by combining measurements of the variation in the depth of the main thermocline (using lESs) with deep current meter observations, one could determine whether meanders extend coherently to the bottom in this region, and, if so, begin to examine in more detail their kinematics and vertical structure.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…During July-November 1982, 135-day records were obtained from an array of three inverted echo sounders (lESs) and six current meters deployed in the Gulf Stream 150 km northeast of Cape Hatteras, N.C. These measurements supplement an earlier data set collected during 1979-80 in this same region (Johns and Watts, 1985; hereafter JW85), but were designed to sample a larger extent of the deep water column than had been done previously. It was hoped that, by combining measurements of the variation in the depth of the main thermocline (using lESs) with deep current meter observations, one could determine whether meanders extend coherently to the bottom in this region, and, if so, begin to examine in more detail their kinematics and vertical structure.…”
Section: Observationsmentioning
confidence: 99%
“…The meandering of the Gulf Stream thermal front is therefore a strongly three-dimensional process in which vertical advection of heat is of leading order. The interested reader is referred to Johns and Watts (1985) for a more detailed mathematical treatment and analysis of the deep kinematic balances.…”
Section: Temperature Structurementioning
confidence: 99%
“…I under Case II) is more typical. Johns and Watts (1985) present a linear analysis of the temperature equation, from data just downstream of Cape Hatteras, which yields results analogous to Case I described here; but in that study, Case I evidently described most of the data, and Case II was not considered at all. The vertical structures shown for Case I and for the baroclinic possibility in Case II resemble that of the first empirical mode for vertical velocity, which accounts for about 80% of the variance (see HI).…”
Section: Introductionmentioning
confidence: 79%
“…The ability to monitor and describe fluctuations in the Gulf Stream and associated rings and eddies is essential for understanding the evolution of such features. Over the past decade, there has been a considerable effort to study the time dependent motion of the Gulf Stream [Brooks and Bane, 1983;Halliwell and Mooers, 1983, Johns and Watts, 1985, 1986Watts and Johns, 1982]. Observations have shown that the Gulf Stream is dominated by change with a broad spectrum of temporal and spatial scales.…”
Section: Introductionmentioning
confidence: 99%